Why stories matter: Exploring learner engagement and metacognition through narratives of the L2 learning experience. (July 2020) - Hiver, Phil; Zhou, Shiyao (Ashlee); Tahmouresi, Somayeh; Sang, Yuan; Papi, Mostafa
Abstract: In this study, we set out to investigate how autobiographical narratives of learners' L2 learning experience are linked to aspects of language learning cognition and behavior. We conducted a Language Learning Story Interview with 41 college learners of foreign languages (Arabic, Mandarin, Spanish). This interview protocol was designed to elicit self-defining scenes from students' language learning experience. Participants then self-reported detailed aspects of their L2 learning engagement and metacognitive capacity—two state-level characteristic adaptations. Using both frequentist and Bayesian analyses for added transparency, we examined the associations across these types of data in order to explore connections between these two levels of language learner psychology. Our analyses provide initial evidence that the emotional, motivational, and cognitive aspects of learners' episodic narratives are associated with important characteristic adaptations to the learning environment. These data also suggest that a narrative mode of inquiry which places a premium on the interpretive value of individual meaning can complement more conventional designs for language learner cognition and engagement.